2016
DOI: 10.1089/vbz.2015.1935
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Genes and the Antimicrobial Susceptibility ofEscherichia coli, Isolated from Wild Waterbirds, in the Netherlands and Poland

Abstract: Affiliation to four phylogroups (A, B1, B2, and D) was examined, among 190 Escherichia coli strains, collected from five, wild waterbird species, including the following: the Greylag goose-Anser anser (61) and the Canada goose-Branta canadensis (33) obtained in the Netherlands, and the Mallard-Anas platyrhynchos (38), the Mute swan-Cygnus olor (37), and the Great cormorant-Phalacrocorax carbo (21) obtained in Poland. Moreover, the prevalence of 10 virulence factors: astA, iss, iucD, irp2, papC, tsh, vat, cva/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
2
9
1
Order By: Relevance
“…Some authors show a high prevalence of this gene among EAEC strains, although the role of IRP-2 in EAEC pathogenesis in unclear [ 34 ]. The irp-2 gene recorded in this study, as well as other genes suggested as predictors of the virulence of APEC strains, i.e., ompT , iutA , iss , pap-C , cva/cvi and tsh , are commonly found in pathogenic E. coli strains from poultry [ 35 ], but have also been reported in E. coli from wild birds [ 36 ]. Kuczkowski et al [ 36 ] demonstrated the frequent occurrence of the irp-2 and astA genes (in 11.6% of isolates), while the iss , iucD , tsh , pap-C and vat genes were rarely found in E. coli isolates from wild water birds in Poland and the Netherlands.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some authors show a high prevalence of this gene among EAEC strains, although the role of IRP-2 in EAEC pathogenesis in unclear [ 34 ]. The irp-2 gene recorded in this study, as well as other genes suggested as predictors of the virulence of APEC strains, i.e., ompT , iutA , iss , pap-C , cva/cvi and tsh , are commonly found in pathogenic E. coli strains from poultry [ 35 ], but have also been reported in E. coli from wild birds [ 36 ]. Kuczkowski et al [ 36 ] demonstrated the frequent occurrence of the irp-2 and astA genes (in 11.6% of isolates), while the iss , iucD , tsh , pap-C and vat genes were rarely found in E. coli isolates from wild water birds in Poland and the Netherlands.…”
Section: Discussionmentioning
confidence: 98%
“…The irp-2 gene recorded in this study, as well as other genes suggested as predictors of the virulence of APEC strains, i.e., ompT , iutA , iss , pap-C , cva/cvi and tsh , are commonly found in pathogenic E. coli strains from poultry [ 35 ], but have also been reported in E. coli from wild birds [ 36 ]. Kuczkowski et al [ 36 ] demonstrated the frequent occurrence of the irp-2 and astA genes (in 11.6% of isolates), while the iss , iucD , tsh , pap-C and vat genes were rarely found in E. coli isolates from wild water birds in Poland and the Netherlands. Borges et al [ 16 ] showed that 30.6% of E. coli isolates taken from wild birds in Brazil were positive for at least one virulence gene, the most prevalent being iss , followed by sitA , traT , ompT , fyuA and irp2 .…”
Section: Discussionmentioning
confidence: 98%
“…[106] However, geese can also carry E. coli strains of human origin (12.5%), and humans and dairy cattle can carry strains of goose origin (2.9 and 14.3% respectively [103]. In a recent study, Kuczkowski and co-workers [107] reported both geographical and interspecific differences (mute swans (n = 37), greylag geese (n = 61) and Canada geese (n = 33) in Poland and the Netherlands, respectively) in the pathogenicity of the E. coli strains identified. An important question to ask is whether E. coli constitutes a normal part of the gastrointrestinal flora of geese and swans, or whether high prevalence of this bacterium in itself is a sign of transmission from anthropogenic sources.…”
Section: Gastrointestinalmentioning
confidence: 99%
“…Birds in this study winter in the UK, and the authors speculated that antibiotic resistance genes may have been picked up in that environment, rather than in the more pristine Svalbard. Recently, Kuczkowski and co-workers [107] found a higher prevalence of antibiotic resistant E. coli strains in birds sampled in Poland compared to geese in the Netherlands, and hypothesized that this may be a result of difference in proximity to human dwellings. However, also other explanations are possible, such as the general level of antimicrobial resistance in the countries in question, and also in the regions where these goose populations spend time during breeding and migration.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…Phylogenetically, E. coli are assigned to seven major phylogenetic groups, namely A, B1, B2, C, D, E and F [21]. Usually, extraintestinal pathogenic strains belong to groups B2 and D, while isolates belonging to groups A and B1 are more often strictly commensal strains from human intestinal microbiota [20,21,34]. Contrary to our present study, where group B1 was mostly isolated in cormorants, most isolated E. coli in mallard ducks were found to belong to group B2 followed by B1 [2].…”
Section: Discussionmentioning
confidence: 99%